Transformation of Internal Thoracic Structures of Callobruchus maculatus (Coleoptera: Bruchidae) from Larva to Adult - Sipei Liu; Xiaokun Liu; Lijie Zhang; Xieshuang Wang; Xinying Zhang; Le Zong; Wenjie Li; Zhengzhong Huang; Xin Liu; Siqin Ge (Insects)
Callobruchus maculatus is a major quarantine pest of stored legumes in China. As a holometabolous insect, it lives inside the bean it burrows into in both its larval and pupal stages. This study utilized micro-CT and 3D reconstruction to document thoracic morphological transformation during larval and pupal stages. The multi-peak fitting of cranial width was applied to determine larval instars. The results indicate that the first-instar larvae bore into beans using prothoracic muscles and those connecting the head to the mesothorax. The second-instar larva possessed the highest number of thoracic muscles, likely correlating with peak boring activity. The prepupa and the initial pupa exhibited minimal musculature, suggesting larval muscle degradation prior to pupation. Muscles unique to prepupae might homologize with indirect flight muscles in pupae, implying that adult flight capability is determined in the final larval stage. The muscles of both larvae and pupae undergo changes in attachment site, shape and curvature throughout development. At the same time, changes also occur in the larval cuticle and pupal endoskeleton. During the larval stage, muscle growth and degradation occur simultaneously, influencing muscle volume. In the pupal stage, the progressive increase in both absolute and relative thoracic muscle volumes prepare the weevil for movement after emergence. Meanwhile, the other thoracic organs, including the gut, air sacs and nerves, also change during development.